2003
DOI: 10.1121/1.1547437
|View full text |Cite
|
Sign up to set email alerts
|

Noise sensitivity and reactions to noise and other environmental conditions

Abstract: This article integrates findings from the literature and new results regarding noise sensitivity. The new results are based on analyses of 28 combined datasets (N = 23,038), and separate analyses of a large aircraft noise study (N = 10,939). Three topics regarding noise sensitivity are discussed, namely, its relationship with noise exposure, its working mechanism, and the scope of its influence. (1) A previous review found that noise sensitivity has no relationship with noise exposure. The current analyses giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
123
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 26 publications
14
123
1
3
Order By: Relevance
“…This is not consistent with one previous study (Miedema and Vos, 2003), which demonstrated that noise sensitivity negatively impacts and disturbs conversations. However, there are significant differences between this study and the previous study in terms of the location of noise exposure and the noise sources.…”
Section: Figure 2 Table IVcontrasting
confidence: 54%
See 4 more Smart Citations
“…This is not consistent with one previous study (Miedema and Vos, 2003), which demonstrated that noise sensitivity negatively impacts and disturbs conversations. However, there are significant differences between this study and the previous study in terms of the location of noise exposure and the noise sources.…”
Section: Figure 2 Table IVcontrasting
confidence: 54%
“…Miedema and Vos (2003) found a significant difference in conversation disturbances between low and high sensitivity groups at high noise exposure levels. A recent study reported that noise sensitivity was related to subjective health complaints such as sleep problems and nervousness (Fyhri and Aasvang, 2010).…”
Section: Hypothesis 2 Lack Of Speech Privacy In Open-plan Offices Ismentioning
confidence: 81%
See 3 more Smart Citations